ASSESSMENT OF LEFT VENTRICULAR DIASTOLIC DYSFUNCTION IN CARDIAC ALLOGRAFT VASCULOPATHY DEVELOPMENT - V. V. Chestukhin; A. B. Mironkov; I. Y. Tyunyaeva; I. G. Ryadovoy; V. M. Zakharevich; B. L. Mironkov (Вестник трансплантологии и искусственных органов)
Aim. The study was aimed to show a possibility of using functional criteria of the allograft left ventricle to assess severity of cardiac vasculopathy. Methods and results. 57 recipients (9 days–15 years after heart transplantati- on) underwent annual follow-up. Left ventricle diastolic function was assessed by determining the velocities of transmitral flow according to echocardiography, coronary state was assessed by coronary angiography. The rela- tionship between the severity of left ventricle diastolic dysfunction and the presence of angiographic evidence of cardiac allograft vasculopathy was revealed. Conclusion. Parameters of left ventricle diastolic dysfunction can be used to determine the severity of pathological changes in myocardium of transplanted heart caused by cardiac allograft vasculopathy.